Effect of Bleaching on Surface Roughness of White Spot Lesions Treated with Different Modalities of Resin Infiltration: An Vitro Study - Aidel Abdullah Alshahrani; Afra Elrashid (Journal of Pharmacy and Bioallied Sciences)
Background: This experimental study evaluated the effect of resin infiltrant (RI) application modalities and bleaching on surface roughness (SR) of the RI white spot lesions (WSLs). Methods: Ninety-six extracted sound premolar teeth were selected, and their coronal part was embedded in a self-cure acrylic resin block. After demineralization, the samples were randomly divided into four study groups (n = 24) based on treatment modalities used: Group 1, etched + RI; Group 2, 1 time etched + 2 times RI; Group 3, 2 times etched + 1 time RI; and Group 4, 2 times etched + 2 times RI. Later all teeth were subjected to bleaching. The SR was assessed using an optical profilometer, post-bleaching, and RI in all groups. Results: Two-way ANOVA confirmed the significance of “Treatment” and the interaction effect between “Group” and “Treatment.” While the t-test confirmed significant differences in SR when compared to the effect of RI and bleaching among the groups (P < 0.05). Conclusion: Bleaching can negatively impact the SR of resin-infiltrated WSLs and affect it significantly.